Maternal Age and Trajectories of Risky Alcohol Use: A Prospective Study. (23rd August 2017) - De Genna, Natacha M.; Goldschmidt, Lidush; Marshal, Michael; Day, Nancy L.; Cornelius, Marie D.
Abstract : Background: No prospective study of maternal alcohol use has focused on age at transition to motherhood as a predictor of trajectories of risky drinking. The goal of this study was to examine the impact of maternal age at first birth on trajectories of alcohol use beyond recommended levels over a 17‐year span. Methods: Pregnant women ( N  = 456) were recruited at an urban prenatal clinic. The women (13 to 42 years old; 64% African American, 36% White) were interviewed about alcohol use during pregnancy and at 6, 10, 14, and 16 years postpartum. Growth mixture modeling (GMM) was used to identify trajectories of risky drinking. Maternal age at first birth was then regressed onto trajectory class membership. Results: The GMM on maternal alcohol use identified 3 groups of mothers as a function of alcohol use before, during, and after the pregnancy. The majority of mothers (66%) were identified as having low‐risk trajectories of alcohol use over the 17‐year span. However, 2 groups were in the higher‐risk categories, with 23% identified as being in a long‐term high‐risk trajectory, and 11% in a short‐term high‐risk trajectory group. Maternal age at first birth predicted membership in a high‐risk group: Younger mothers were more likely to be classified into a long‐term high‐risk alcohol use group. Conclusions: Younger mothers were more likely to engage in risky drinking early in pregnancy, continuing 6 to 14 years postpartum. These results can help physicians target mothers who are likely to exceed current NIAAA guidelines of abstinence during pregnancy, and no more than 7 drinks per week in the postpartum. Abstract : These findings predict which women are more likely to exhibit risky drinking before, during and after a pregnancy, and ultimately, who is at greater risk of alcohol use disorder. Younger mothers and those who used marijuana during pregnancy were more likely to be long‐term high‐risk drinkers (see trajectory groups in Figure1 ). These results can help physicians target the women most likely to exceed current NIAAA guidelines of abstinence during pregnancy and 7 drinks per week for non‐pregnant women.